1981
DOI: 10.1246/bcsj.54.754
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relations in the System PbO–PbSiO3

Abstract: Phase relations in the system PbO–PbSiO3 were determined at temperatures above 650 °C. Two new lead silicate phases, Pb5SiO7 and Pb11Si3O17 were found to be stable. The former melts incongruently at 733±1 °C to solid PbO plus liquid, and decomposes below 702±1 °C. The latter melts congruently at 728±1 °C. The compound Pb4SiO6, which has been accepted as stable, could not be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

1981
1981
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…-A haute température, près de la courbe de liquidus : Pb2SiO4 (cyclosilicate de plomb, à fusion congruente), Pb11Si3O17 (à fusion congruente) et Pb5SiO7 (à fusion non congruente). La phase Pb4SiO6 reportée dans les diagrammes de phase plus anciens (Smart et Gasser 1974) ne serait pas stable (Hirota et Hasegawa 1981).…”
Section: Launclassified
See 2 more Smart Citations
“…-A haute température, près de la courbe de liquidus : Pb2SiO4 (cyclosilicate de plomb, à fusion congruente), Pb11Si3O17 (à fusion congruente) et Pb5SiO7 (à fusion non congruente). La phase Pb4SiO6 reportée dans les diagrammes de phase plus anciens (Smart et Gasser 1974) ne serait pas stable (Hirota et Hasegawa 1981).…”
Section: Launclassified
“…Nous présenterons ici des éléments sur l'évolution de la structure des phases cristallines mixtes mentionnées dans le paragraphe précédent en fonction de la teneur en oxyde de plomb en nous basant sur les déterminations structurales reportées dans la littérature 3 (mol% PbO): l'alamosite PbSiO3 (50%) (Boucher et Peacor 1968), Pb7Si6O19 (53,8%) (Siidra et al 2014), Pb3Si2O7 (60%) (Petter et Harnik 1971), Pb2SiO4 (66,6%) (Dent Glasser et al 1981), Pb11Si3O17 (78,6%) (Hirota et Hasegawa 1981 ;Kato 1982). Trois de ces structures sont représentées en figure 3.7.…”
Section: Les Phases Cristallines Du Système Binaire Sio2-pbounclassified
See 1 more Smart Citation
“…The PbO-SiO 2 binary system contains the primary phase fields of cristobalite, tridymite (SiO 2 ), PbSiO 3 , Pb 2 SiO 4 , Pb 11 Si 3 O 17, Pb 5 SiO 7 and PbO. [18][19][20][21][22][23][24] Following a critical analysis of the experimental and thermodynamic data available on the PbO-SiO 2 binary and further experimental measurements, Jak et al [22] described this system using an optimized thermodynamic database. Subsequent experimental studies by Shevchenko and Jak [23] have demonstrated that there is, in fact, no liquid immiscibility in the PbO-SiO 2 binary in the high-silica region of the PbO-SiO 2 binary, and the liquidus in the cristobalite/tridymite primary phase field is in agreement with that previously reported by Hirota.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent experimental studies by Shevchenko and Jak [23] have demonstrated that there is, in fact, no liquid immiscibility in the PbO-SiO 2 binary in the high-silica region of the PbO-SiO 2 binary, and the liquidus in the cristobalite/tridymite primary phase field is in agreement with that previously reported by Hirota. [24] The MgO-SiO 2 binary system contains the primary phase fields of periclase (MgO), olivine (forsterite Mg 2 SiO 4 ), pyroxene (protoenstatite MgSiO 3 ) and cristobalite (SiO 2 ), with liquid-liquid immiscibility in the high silica region. Experimental phase equilibria data for this system were reported by [25][26][27][28][29] and the system described by thermodynamic models.…”
Section: Introductionmentioning
confidence: 99%